2019
DOI: 10.2320/matertrans.me201905
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of the Silicate Containing CaTiO<sub>3</sub> Film with Hydrophilic and Smooth Surface on Titanium to Improve Osteoconductivity

Abstract: It has been reported that hydrophilicity and hydrophobicity of implants influenced the bioactivity. However, it is hard to maintain the hydrophilicity in case of being stored in air. So it is critical to find a way to maintain implants' hydrophilicity. In general, silicate has been known to contribute the hydrophilicity. In this study, the silicate containing CaTiO 3 films have been prepared on Ti substrates by two-step treatment for biomaterial applications. The hydrophilicity, osteoconductivity and protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because of their exceptional mechanical qualities, superior biocompatibility, and excellent corrosion resistance, commercially pure titanium and Ti-based alloys have been widely employed in hard tissue replacement metallic implants, especially in the orthopedic and dental professions [5][6][7][8]. Among the most recommended reasons for boneimplant failure are stress shielding, inadequate osseointegration, and a high potential for bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their exceptional mechanical qualities, superior biocompatibility, and excellent corrosion resistance, commercially pure titanium and Ti-based alloys have been widely employed in hard tissue replacement metallic implants, especially in the orthopedic and dental professions [5][6][7][8]. Among the most recommended reasons for boneimplant failure are stress shielding, inadequate osseointegration, and a high potential for bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accelerate and achieve earlier and better osseointegration, Ti and Ti alloys with different surfaces micro-scale topographies produced by acid-etching, sandblasting and anodization have been developed and it has been proved that micro-scale topography could promote the adhesion, differentiation, extracellular matrix formation and mineralization of osteoblasts [16][17][18]. Other studies also showed that surface roughness and hydrophilicity could obviously in uence osteoconductivity of Ti by altering protein adsorption and cell adhesion after implantation [19]. Recently, it was reported that the charge properties and the charge density of the material surface could affect the cell growth and cell reaction, because of the electrostatic interaction between a positively charged material surface and a negatively charged cell membrane.…”
Section: Introductionmentioning
confidence: 99%